Lost at sea: The euro needs a Euro Treasury - Jörg Bibow (Levy Economics Institute of Bard College, 2013)
The euro crisis remains unresolved even as financial markets may seem calm for now. The current euro regime is inherently flawed, and recent reforms have failed to turn this dysfunctional regime into a viable one. Our investigation is informed by the "cartalist" critique of traditional "optimum currency area" theory (Goodhart 1998). Various proposals to rescue the euro are assessed and found lacking. A "Euro Treasury" scheme operating on a strict rule and specifically designed not to be a transfer union is proposed here as a condition sine qua non for healing the euro's potentially fatal birth defects. The Euro Treasury proposed here is the missing element that will mend the current fiscal regime, which is unworkable without it. The proposed scheme would end the currently unfolding euro calamity by switching policy from a public thrift campaign that can only impoverish Europe to a public investment campaign designed to secure Europe's future. No mutualization of existing national public debts is involved. Instead, the Euro Treasury is established as a means to pool eurozone public investment spending and have it funded by proper eurozone treasury securities.
Keywords: E02; E42; E58; E61; E62; F36; G01; 330; Euro Crisis; Currency Union; Fiscal Union; Transfer Union; Cartalism; Lender of Last Resort; European Integration